Analysis of Sanitation Hygiene and the Presence of Escherichia coli in Side Dishes at Restaurants in the Sunggal Area, Medan - Indah Rizqika; Syafran Arrazy (Karya Kesehatan Siwalima, 2026)
Foodborne illness remains a significant public health concern, with Escherichia coli contamination being one of the major causes. This study aims to describe the sanitation and hygiene conditions of restaurants and the presence of E. coli in side dishes in Sunggal Village, Medan Sunggal District. A descriptive research design was employed, using observation and laboratory examination methods conducted at the Medan Health Polytechnic laboratory. The study population comprised all 18 restaurants in Sunggal Village, while fried chicken samples were selected for laboratory analysis. Data were collected through direct observation using a sanitation and hygiene checklist, as well as laboratory testing of side dish samples to detect E. coli using Endo Agar media. The results showed that most restaurants did not meet sanitation and hygiene standards, particularly in terms of food handler personal hygiene, equipment sanitation, water sources, and food selection and presentation. Laboratory findings indicated that while most samples tested negative, several samples were positive for E. coli. In conclusion, the sanitation and hygiene conditions of restaurants in Sunggal Village remain suboptimal, and there is still a risk of E. coli contamination. Strengthened guidance and supervision are therefore necessary to improve food safety in the community.